Alpha-lipoic acid attenuates cardiac hypertrophy via inhibition of C/EBPβ activation. (5th January 2015) - Zou, Jian; Gan, Xiaohong; Zhou, Houfeng; Chen, Xiaoxiao; Guo, Yuanxin; Chen, Jia; Yang, Xiaolai; Lei, Jianguo
Highlights: ALA attenuates cardiomyocyte hypertrophy induced by PE. ALA inhibits cardiac hypertrophy induced by CAL. ALA treatment significantly inhibits the activation of C/EBPβ. Abstract: Alpha-lipoic acid (ALA), a naturally occurring compound, exerts powerful protective effects in numerous cardiovascular disease models. However, the pharmacological property of ALA on cardiac hypertrophy has not been well investigated. The present study was carried out to determine whether ALA exerts a direct anti-hypertrophic effect in cultured cardiomyocytes and whether it modifies the hypertrophic process in vivo . Furthermore, we determined the potential underlying mechanisms for these actions. Treatment of cardiomyocytes with phenylephrine (PE) for 24 h produced a marked hypertrophic effect as evidenced by significantly increased in ANF and BNP mRNA levels, as well as cell surface area. These effects were attenuated by ALA in a concentration-dependent manner with a complete inhibition of hypertrophy at a concentration of 100  µ g/mL. PE-induced cardiomyocyte hypertrophy was associated with increased mRNA and protein levels of C/EBPβ, which were inhibited by pretreatment with ALA. However, when cardiomyocytes were co-transfected with C/EBPβ, ALA failed to inhibit hypertrophic responses. Upregulation of C/EBPβ expression was also evident in rats subjected to 4 weeks of coronary artery ligation (CAL). However, rats treated with ALA demonstrated markedly reduced hemodynamic and hypertrophic responses, which were accompanied by attenuation of upregulation of C/EBPβ. Taken together, our results revealed a robust anti-hypertrophic and anti-remodeling effect of ALA, which is mediated by inhibition of C/EBPβ activation.